2019
DOI: 10.1097/md.0000000000017281
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ultrasound diagnosis for chronic pelvic pain

Abstract: Background:This study aims to assess the impact of ultrasound diagnosis in patients with chronic pelvic pain (CPP).Methods:We will carry out a comprehensive electronic search from the databases below: PUBMED, EMBASE, Cochrane Library, PSYCINFO, Web of Science, Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, and WANGFANG databases from inception to July 1, 2019. The case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A recent systematic review showed modest evidence of the diagnostic accuracy of ultrasound in patients with CPP [16], despite the recommendations as a first-line test in the evaluation of the female pelvices [18,19]. At least in part, this may be due to the absence of consensual protocols for obtaining images and reports, which prevents a more precise conclusion about the usefulness or real limitation of the method in this population.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review showed modest evidence of the diagnostic accuracy of ultrasound in patients with CPP [16], despite the recommendations as a first-line test in the evaluation of the female pelvices [18,19]. At least in part, this may be due to the absence of consensual protocols for obtaining images and reports, which prevents a more precise conclusion about the usefulness or real limitation of the method in this population.…”
Section: Introductionmentioning
confidence: 99%